Stakeholder Perspectives on EU Regulatory Frameworks: Navigating Critical Raw Materials, Battery Innovation, and Recycling Challenges [version 2; peer review: 2 approved] - Willem Arie Vonk; Anish Patil (Open Research Europe)
Background The European Union's Green Deal Industrial Plan (GDIP), introduced in 2023, aims to advance sustainability, energy independence, and carbon neutrality by 2050. Supported by the Net-Zero Industry Act (NZIA) and the Critical Raw Materials Act (CRMA), the GDIP seeks to boost clean technology manufacturing, particularly in sectors like electric vehicles (EVs), while ensuring a secure supply of critical raw materials. Additionally, the EU Battery Regulation 2023 establishes strict lifecycle management requirements to promote circularity in the battery sector. However, policy fragmentation, regulatory complexity, and stakeholder concerns pose challenges to achieving these objectives. Methods This study examines the coherence of the GDIP and its associated policies, assessing whether they form a unified framework or introduce contradictions that hinder progress. Through stakeholder analysis, the research explores perceptions of regulatory effectiveness, industrial competitiveness, and the role of workforce skills in facilitating the green transition. Results Findings indicate that while these policies share common objectives, they exhibit overlaps and inconsistencies that create barriers to investment and innovation. Stakeholders express concerns about regulatory clarity and feasibility, emphasizing the need for realistic targets, streamlined processes, and greater social acceptance of industrial projects. The research also highlights a critical skills gap in green technologies, underlining the necessity of workforce development initiatives to support the transition. Conclusions For the GDIP to achieve its full potential, EU policies must be better aligned, with clearer regulatory frameworks and stronger stakeholder engagement. Addressing the skills shortage, promoting industrial careers, and leveraging tools like the European battery passport will be crucial in fostering collaboration and ensuring successful implementation of the EU’s green industrial ambitions.